Building Interdisciplinary Biomedical Research Using Novel Collaboratives - Ravid, Katya (Acad Med, 2013)
Traditionally, biomedical research has been carried out mainly within departmental boundaries. However, successful biomedical research increasingly relies on development of methods and concepts crossing these boundaries, requiring expertise in different disciplines. Recently, major research institutes have begun experimenting with ways to foster an interdisciplinary ethos. The Evans Center for Interdisciplinary Biomedical Research (“the Evans Center”) at Boston University is a new organizational paradigm to address this challenge. The Evans Center is built around interdisciplinary research groups termed affinity research collaboratives (ARCs). Each ARC consists of investigators from several academic departments and at least two research disciplines, bound by a common goal to investigate biomedical problems concerning human disease. Novel aspects of the Evans Center include a “bottom-up” approach to identifying areas of ARC research (research vision and strategy are typically initiated by a core group of faculty with input from the center director); a pre-ARC period of faculty affiliation/project(s)’ self-selection prior to formation of a peer-reviewed ARC; and Evans Center support for innovative ARCs for up to 3 years pending yearly metric evaluation, followed by continued administrative support as a group matures into an ARC-Program.